Being an international university student in Turkey: comparative field study on city population and Turkish and international students - Bacanli, Hasan; Erisen, Yavuz; Celikoz, Nadir; Dombayci, Mehmet Ali; Karadag, Engin; Toprak, Metin; Sahin, Mehmet; Kirecci, M. Akif (TUBA-TURKISH ACAD SCIENCES, 2016)
In this study, we aimed to investigate comparatively the attitudes of Turkish and international university students towards the city they have their education and of the city population towards these students. We designed the study in cross-sectional pattern and used survey research as quantitative research approach. The sample of the study included 1055 international university students, 1306 Turkish university students and 1003 individuals living in the cities that these students have their education. The data of the study were obtained through three attitudinal scale developed for the study, and these data were analyzed by t-test and ANOVA analysis. The findings indicated that the attitudes of Turkish students towards the city were at mid-level and of international students were at mid-high level while the attitudes of the citizens towards university students were at low-mid level. Also, having education in cities known to be student cities (i.e. Bursa, Izmir, Eskiflehir) by the people provides a positive contribution to the attitudes of students towards the city. On the other hand, the cities with high living standards and transportation and accommodation problems such as Istanbul provide a negative contribution to the attitudes of students towards the city. In conclusion, in order to improve the quality of university education, it is important not only to improve the physical structures and educational content but also to develop the attitudes of people living in related city towards students positively.
Keywords: City population; attitude; internationalization; international student; university; CONFIRMATORY FACTOR-ANALYSIS; OF-FIT INDEXES; Education & Educational Research